The Use of CIRC (Cooperative Integrated Reading and Composition) Learning Model-Based Comics to Improve Arabic Text Reading Skills in Junior High School Students | Penggunaan Komik Berbasis Model Pembelajaran CIRC untuk Meningkatkan Keterampilan Membaca Teks Bahasa Arab pada Siswa Madrasah Tsanawiyah - Sodik , Achmad Ja'far; Janah, Sofiah Iskanatin; syukran, syukran (ATHLA : Journal of Arabic Teaching, Linguistic and Literature, 2023)
This study aims to find out whether comic media based on the CIRC learning model can improve the reading skills of Arabic texts of students in class VII mts N 6 Boyolali or not. This research was conducted because of several problems including different backgrounds and abilities of students, lack of student activity during learning, then inappropriate media and learning models and the average score of Arabic reading skills is lower than other skill scores, even these scores have not met the minimum completion criteria (KKM) with a minimum score of 69. This study aims to find out whether comic media based on the CIRC learning model can improve the reading skills of Arabic texts of students in class VII mts N 6 Boyolali or not. The results showed that the average pre-test and post-test scores in the experimental class were 50.16 and 81.90 with an increase of 31.74. Meanwhile, the average scores of pre-test and post-test in the control class were 50.31 and 68.06 for post-test with an increase of 17.75. From these results, the experimental class experienced a fairly high increase compared to the control class. Then the results of obtaining hypothesis testing by using the t-test, namely with a significance level of 0.05, the calculated t value = 5.315 is obtained greater than t table = 1.995 which means ho is rejected and ha is accepted.